Second Language Aquisition and The Development through Nature-Nurture - Syahfitri Purnama (JETL (Journal of Education, Teaching and Learning), 2017)
There are some factors regarding which aspect of second language acquisition is affected by individual learner factors, age, learning style. aptitude, motivation, and personality. This research is about English language acquisition of fourth-year child by nature and nurture. The child acquired her second language acquisition at home and also in one of the courses in Jakarta. She schooled by her parents in order to be able to speak English well as a target language for her future time. The purpose of this paper is to see and examine individual learner difference especially in using English as a second language. This study is a library research and retrieved data collected, recorded, transcribed, and analyzed descriptively. The results can be concluded: the child is able to communicate well and also able to construct simple sentences, complex sentences, sentence statement, phrase questions, and explain something when her teacher asks her at school. She is able to communicate by making a simple sentence or compound sentence in well-form (two clauses or three clauses), even though she still not focus to use the past tense form and sometimes she forgets to put bound morpheme -s in third person singular but she can use turn-taking in her utterances. It is a very long process since the child does the second language acquisition. The family and teacher should participate and assist the child, the proven child can learn the first and the second language at the same time.